NATURAL STRESS CONCENTRATION IN STRUCTURALLY HETEROGENEOUS MASSIVES OF ORE DEPOSITS IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article deals with rock massifs of structurally heterogeneous ore deposits in Kyrgyzstan. The data of long-term full-scale experimental studies of the stress-strain state of rock masses are summarized and the results of diagnostics of local zones of natural stress concentrations are presented.
Keywords: structural heterogeneity, tectonic disturbances, stress concentration, diagnostics